Inflation and Income Inequality in Riau Province - Asrofillah, Muhammad Fuad; Arimurti, Rizqa (Politeknik Negeri Bengkalis, 2024)
This study investigates the relationship between inflation, economic growth, and income inequality, focusingon the Riau province. This research uses panel data from 12 districts / cities in Riau province with the period 2018-2022and uses the granger causality test with EViews 13 software. The findings reveal no causal relationship between inflationand income inequality during the observed period, indicating that fluctuations in inflation rates do not predict changes inincome inequality, nor vice versa. This conclusion highlights the significance of government policy, economic structure,education, and labor force participation over inflation. While some studies suggest that moderate inflation may reduceinequality by increasing the value of assets held by lower-income groups, this effect is context-dependent. Furthermore,the analysis of economic growth reveals a complex relationship with income inequality, where the Granger causality testshows no predictive link, especially in developing nations where growth benefits often favor high-income groups.Although some research identifies a causal relationship under specific circumstances, the overall implication is thattargeted policy interventions addressing labor market dynamics and redistribution are essential for mitigating incomeinequality, rather than relying solely on economic growth. The study emphasizes the need for context-specific approachesto understand and address income inequality effectively.